Poverty and dependency in Cape Town : a sociological study of 3,300 dependents receiving assistance from the Cape Town General Board of Aid - Wagner, O. J. M. (Oloff Jacobus Marais),1904- (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 1936.